On the Question of the Semantic-Functional Relationship between the Կ(Ը)- Future and the -ՈՒ Future in Modern Eastern Armenian - Avetyan, Sargis (Bulletin of Yerevan University B: Philology, 2022)
It is argued that attempts at characterizing the կ(ը)- future (կգնամ, կխոսեմ) in Modern Eastern Armenian as pertaining to the so-called Hypothetical mood (ենթադրական եղանակ) or the Conditional mood (պայմանական եղանակ) is not justified from the General linguistic and typological perspective. The following considerations are of great importance: 1) as pointed out by a number of scholars, the future tense, in distinction from the present tense and the past tense, is never a purely temporal category; it is partly temporal and partly modal. Interestingly enough, future tense markers often arise diachronically from elements which initially were used to express various modal meanings. On the other hand, future tense forms tend to serve modal functions as well; 2) the կ(ը)- future in Modern Eastern Armenian does not differ in any significant way from the future indicative in other languages from the semantic-functional viewpoint; 3) the use of the կ(ը)- future in conditional constructions is not its primary function as is usually the case with the typical Conditional mood. As to the semantic-functional content of the -ու future (գնալու եմ, խոսելու եմ) in Modern Eastern Armenian, it corresponds to the typological characterization of the expected future (or predestined future), and, accordingly, should be viewed on a par with the latter. Therefore, the semantic-functional relationship between the կ(ը)- future and the -ու future should be regarded as a contrast between the simple future tense and the expected future (or predestined future) tense, respectively.